2016
DOI: 10.3354/cr01418
|View full text |Cite
|
Sign up to set email alerts
|

Global warming-induced changes in climate zones based on CMIP5 projections

Abstract: Climate classifications can provide an effective tool for integrated assessment of climate model results. We present an analysis of future global climate projections performed in the framework of the Coupled Model Intercomparison Project Phase 5 (CMIP5) project by means of Köppen-Trewartha classification. Maps of future climate type distributions were created along with the analysis of the ensemble spread. The simulations under scenarios with representative concentration pathway (RCP) 4.5 and RCP8.5 showed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 22 publications
2
42
1
Order By: Relevance
“…This result was confirmed by Rubel and Kottek (2010), who investigated denser data sets of observed data, global circulation models and emission scenarios. The most recent studies based on the newest global climate model simulations from CMIP5 ensemble (e.g., Mahlstein et al, 2013;Feng et al, 2014;Belda et al, 2016) and using the Köppen-Trewartha classification reported a retreat of polar climate zones and expanding warmer and drier types. The authors also pointed out the large uncertainty among models (Mahlstein et al, 2013;Belda et al, 2016) and attributed the projected shifts of climate types during the 21st century mainly to temperature changes (Feng et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This result was confirmed by Rubel and Kottek (2010), who investigated denser data sets of observed data, global circulation models and emission scenarios. The most recent studies based on the newest global climate model simulations from CMIP5 ensemble (e.g., Mahlstein et al, 2013;Feng et al, 2014;Belda et al, 2016) and using the Köppen-Trewartha classification reported a retreat of polar climate zones and expanding warmer and drier types. The authors also pointed out the large uncertainty among models (Mahlstein et al, 2013;Belda et al, 2016) and attributed the projected shifts of climate types during the 21st century mainly to temperature changes (Feng et al, 2014).…”
mentioning
confidence: 99%
“…The most recent studies based on the newest global climate model simulations from CMIP5 ensemble (e.g., Mahlstein et al, 2013;Feng et al, 2014;Belda et al, 2016) and using the Köppen-Trewartha classification reported a retreat of polar climate zones and expanding warmer and drier types. The authors also pointed out the large uncertainty among models (Mahlstein et al, 2013;Belda et al, 2016) and attributed the projected shifts of climate types during the 21st century mainly to temperature changes (Feng et al, 2014). Another study of Alessandri et al (2014) focused on the assessment of Mediterranean climate from the CMIP5 model ensemble during the 21st century and found polewards shifts of KGC subtypes Csa and Csb based on RCP4.5 (medium-low) greenhouse gases concentration scenario.…”
mentioning
confidence: 99%
“…Both the agreement in major change and differences between climate change projections are visually combined ( figures 1-4), facilitating the interpretation of complex uncertainty. The data reported here present a major advance over earlier attempts at mapping bioclimate shifts (e.g Alessandri et al 2014, Beck et al 2005, Belda et al 2016, Jylhä et al 2010, Leemans et al 1996, Mahlstein et al 2013, Metzger et al 2008, Rohli et al 2015, Saxon et al 2005, Wang and Overland 2004 due to its greater thematic resolution (125 strata) and spatial resolution (5 arcmin). Its global coverage also provides consistency for comparative analyses, and provides the potential for the dataset to be used as a consistent tool for global assessments.…”
Section: Discussionmentioning
confidence: 72%
“…Then, this ratio is multiplied by the observed data. This delta method is commonly used in climate change studies for the analysis of future changes of Köppen climate zones (Gao and Giorgi, 2008;Mahlstein et al, 2013;Feng et al, 2014;Belda et al, 2016; and many others).…”
Section: Model Description and Simulations Designmentioning
confidence: 99%